The Relationship between Parental Involvement and Memorization Ability Al-Qur’an students in RTQ Mujahidin Nagari Api-Api Kabupaten Pesisir Selatan - Nesya, Amanda Yulia; Ismaniar, Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This research was motivated by the low ability to memorize the Al-Qur'an of students at RTQ Mujahidin Nagari Api-Api. This is thought to be due to a lack of parental involvement. This is due to the low involvement of parents in students' memorization abilities. This research aims to; find out the description of parental involvement, the description of students' memorization abilities and the relationship between parental involvement and students' Al-Qur'an memorization abilities in RTQ Mujahidin Nagari Api-Api, Pesisir Selatan Regency. This research uses a quantitative approach with a correlational type. The population in this study were 37 parents of santri at RTQ Mujahidin while the sample was 30 parents of santri. This research sample was taken using area random sampling. The data collection technique is in the form of a questionnaire with the tool being a questionnaire. Data analysis techniques use percentage and product moment formulas. The results of this research show that: (1) parental involvement is in the low category, (2) the students' ability to memorize the Al-Qur'an is also in the low category, and (3) there is a significant relationship between parental involvement and the students' Al-Qur'an memorization ability in RTQ Mujahidin Nagari Api-Api, Pesisir Selatan Regency. It is recommended for parents to: (1) improve children's memorization abilities by listening to children learn, (2) establish harmonious communication with children so as to support the optimal development of children's memorization abilities, (3) As well as for other researchers to look at additional phenomena related to children's memorization development by using different variables.Keywords: Parental Involvement, Al-Qur'an Memorizing Ability, Santri.